Influence of Agroclimatic Conditions on Active Substances Content in Hemp Cultivated in the South-East Baltic Region - Joanna Poniatowska; Katarzyna Panasiewicz; Karolina Wielgus; Milena Szalata; Bogusława Jaśkiewicz (Journal of Natural Fibers, 2022)
Influence of agroclimatic conditions on active substances content in hemp cultivated in the South-East Baltic region Abstract: Due to legal regulations prohibiting cultivation of cannabis (Cannabis indica Lam.) in many countries, industrial hemp (Cannabis sativa L.) remains the main source of active substances with potential application in the pharmaceutical industry. To assess the possibility of using the varieties of industrial hemp for this goal, and their adaptation to the habitat conditions and the agricultural technology appropriate for them, we investigated three monoecious varieties of hemp (‘Futura 75,’ ‘KC Dora’ and ‘Tygra’) at different sowing densities (60 germinating seeds·1 m2 or 180 germinating seeds·1 m2) and nitrogen fertilization levels (0, 30, 60, 90 kg·ha−1). In none of the tested hemp varieties registered as fibrous did the concentration of Δ9-THC exceed 0.2%, satisfying the requirements of European legislation for industrial hemp varieties. The tested varieties did not differ significantly in the cannabidiol (CBD) and Δ9- tetrahydrocannabinol (Δ9 -THC) content in the dry matter of inflorescences. Agronomic factors such as sowing density or nitrogen fertilization did not modify the content of CBD and Δ9-THC. This result is very helpful for farmers, because it allows them to select hemp varieties of dual-purpose production (stems and inflorescences or stems and seeds) adapted to the South-East Baltic environment.